2012
DOI: 10.3892/or.2012.2001
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical biodistribution and safety study of reduced expression in immortalized cells/Dickkopf-3-encoding adenoviral vector for prostate cancer gene therapy

Abstract: The biodistribution and safety of adenoviral vectors encoding the human REIC/Dkk-3 tumor suppressor gene (Ad-REIC) were examined in this preclinical study for in situ prostate cancer gene therapy. First, the in vitro apoptotic effects of Ad-REIC in normal and cancer cells derived from the prostate and liver were examined. Significant apoptotic effects were observed at 100 MOI (multiplicity of infection) in prostate cancer cells (LNCaP, PC3) and hepatoma cells (HEP3B and HEPG2); however, no effects were seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As for administration strategy, local administration might be preferable rather than systemic administration to minimize the adverse effect in clinical situations. We previously confirmed in mouse model that Ad-REIC could be widely distributed in the bodies after intratumoral local administration, and local administration was effective not only directly but also indirectly through the immune system effect [16], [23]. In addition, intrapleural local administration could be another administration strategy for the patients with malignant pleural effusions.…”
Section: Discussionmentioning
confidence: 82%
“…As for administration strategy, local administration might be preferable rather than systemic administration to minimize the adverse effect in clinical situations. We previously confirmed in mouse model that Ad-REIC could be widely distributed in the bodies after intratumoral local administration, and local administration was effective not only directly but also indirectly through the immune system effect [16], [23]. In addition, intrapleural local administration could be another administration strategy for the patients with malignant pleural effusions.…”
Section: Discussionmentioning
confidence: 82%
“…Attenuation of TGF‐β signaling in prostate cancer following CRISPR‐mediated reactivation of DKK3 expression has been reported . Gene therapy with DKK3 has been proposed for treatment of prostate cancer (NCT01931046) …”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus-mediated gene delivery continues to be the preferred treatment for cancer as the vectors indicate the high transduction efficacy of the therapeutic gene and the safety of the procedure when used for direct local injection (57). A number of previous clinical trials have demonstrated the utility and safety of the intratumoral injection of adenoviral vectors in cancer lesions (7).…”
Section: Introductionmentioning
confidence: 99%